GERAKAN HIJAU SEKOLAH: UPAYA MENJAGA EKOSISTEM LINGKUNGAN MELALUI PENANAMAN POHON - Mutmainah, Mutmainah; Ardianto, Ardianto; Reksamunandar, Rhyan Prayuddy; Syah, Ilham; Anuli, Wildan Y; Asma, Andi; Kadir, Kadir; Santoso, Agung Budi; Cahyani, Dwi; Bachdar, Aditya Jibril Zahran; Idji, Dinda Rahmawati Anugrah; Zahratusitha Timbulus, Nazwa (Mafaza : Jurnal Pengabdian Masyarakat, 2025)
The program aims to foster students’ eco-theological awareness through tree-planting activities as a form of responsibility toward God’s creation, while also creating a green, healthy, and spiritually enriched school environment. The activity took place at Al-Faqih Foundation Kauditan, North Minahasa, on September 18, 2025, involving the foundation board, school leaders, teachers, and students in a spirit of collaboration to care for the environment. The program included several stages: planning, socialization and education, tree planting, as well as evaluation and reflection to strengthen understanding and participation among all stakeholders. The results showed a significant increase in environmental awareness, with about 80% of students actively participating in the planting activities and 90% of teachers supporting the ongoing initiatives. Through the planting of 75 tree seedlings around the school area, the learning atmosphere has become greener, fresher, and more enriched with educational and spiritual values. This program is designed to be sustainable, with regular tree maintenance and continued student involvement in environmental activities to nurture spiritual awareness and ecological responsibility as part of daily school life.